2021
DOI: 10.1021/acssynbio.0c00568
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Production of Menaquinone-7 from Glucose by Metabolically Engineered Escherichia coli

Abstract: Menaquinone-7 (MK-7) possesses wide health and medical value, and the market demand for MK-7 has increased. Metabolic engineering for MK-7 production in Escherichia coli still remains challenging due to the characteristics of the competing quinone synthesis, and cells mainly synthesized menaquinones under anaerobic conditions. To increase the production of MK-7 in engineered E. coli strains under aerobic conditions, we divided the whole MK-7 biosynthetic pathway into three modules (MVA pathway, DHNA pathway, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Nevertheless, a recent example of efficient menaquinone-7 (MK 7 ) production to a titer of 1350 mg/L has shown that quinone production by E. coli should not be underestimated. This was achieved by optimized heterologous expression of MVA pathway genes and screening several heterologous Idi enzymes to improve IPP supply, overexpression of endogenous and exogenous MK pathway genes and enhancing the flux from chorismate to 1,4-dihydroxy-2-naphthoate, the direct precursor for demethylmenaquinone (Gao et al 2021 ).…”
Section: Strategies To Improve Ubiquinone-related Production In Micro...mentioning
confidence: 99%
“…Nevertheless, a recent example of efficient menaquinone-7 (MK 7 ) production to a titer of 1350 mg/L has shown that quinone production by E. coli should not be underestimated. This was achieved by optimized heterologous expression of MVA pathway genes and screening several heterologous Idi enzymes to improve IPP supply, overexpression of endogenous and exogenous MK pathway genes and enhancing the flux from chorismate to 1,4-dihydroxy-2-naphthoate, the direct precursor for demethylmenaquinone (Gao et al 2021 ).…”
Section: Strategies To Improve Ubiquinone-related Production In Micro...mentioning
confidence: 99%
“…E. coli can be used to produce MK-7, even if E. coli mainly produces Q-8, MK-8, and demethylmenaquinone-8 (DMK-8) [ 116 ]. Recently, Gao et al (2021) produced MK-7 by E. coli through systematic metabolic engineering [ 100 ]. The authors categorized the MK-7 biosynthesis pathway of E. coli into three modules: the MVA pathway, the DHNA pathway, and the MK-7 pathway, and optimized each pathway to enhance MK-7 production.…”
Section: Production Of Vitamin K Using Engineered Microorganismsmentioning
confidence: 99%
“…They first overexpressed the isopentenyl diphosphate isomerase (Idi) enzyme from different species, Saccharomyces cerevisiae, Populus trichocarpa , and E. coli K12, which are involved in the supply of IPP/DMAPP precursor for the biosynthesis of MK-7. Next, they overexpressed the endogenous MenA and exogenous UbiE together with the heptaprenyl pyrophosphate synthase (HepPPS) from B. subtilis which enhanced MK-7 production up to 70 μM [ 100 ]. The HepPPS is an important key enzyme, allowing MK-7 production in E. coli under aerobic conditions.…”
Section: Production Of Vitamin K Using Engineered Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations